Métodos alternativos para controle de doenças fúngicas na cultura de jambu (Spilanthes oleraceae L.) através de Equisetum spp e preparado biodinâmico 501 - Bertalot, Maria José Alves; Carvalho-Pupatto, Juliana Garcia; Furtado, Edson Luiz [UNESP]; Rosa, Daniel Dias [UNESP]; Mendoza, Eduardo; Lima, Adriano Balarim de (My University, 2010)
The action of the must (Tecaphora spilanthes) and black flower of jambu (Alternaria solani) constitute a serious plant pathologic problem in the intensive culture of jambu (Spilanthes oleraceae L.). This work had as objective to evaluate the performance of method of alternative control of the illnesses caused for these fungus through the influence of silicon. The experiment followed a randomized block design with six treatments and five repetitions, in field conditions in a farm near from Botucatu/SP. The treatments were: 1- no application-control; 2-Water; 3-Preparation of Equisetum arvense; 4-Preparation of Equisetum hyemale; 5-Preparation of Equisetum giganteum; 6- Biodynamic preparation 501 (horn-silica). It was observed a trend of treatment 6 (Biodynamic Preparation 501 - silica) to show the biggest efficiency in the control in the number as in the note of sick flowers and galls. In the case of the number of galls and ranking of galls, treatment 4 presented minor influence in relation to treatments 3, 5 and 6. Biodynamic preparation 501 (treatment 6), with high silica content, had greater effectiveness in the control of the smut (Tecaphora spilanthes) and black flower of jambu (Alternaria solani).

A ocorrência do fungo do carvão ou galha (Tecaphora spilanthes) e da flor preta do jambu (Alternaria solani) constituem sério problema fitossanitário na cultura intensiva do jambu (Spilanthes oleraceae L.). Este trabalho teve como objetivo avaliar o desempenho do método de controle alternativo das doenças causadas por estes fungos através da atuação do preparado de Equisetum spp. O delineamento utilizado foi em blocos ao acaso com seis tratamentos e cinco repetições, em condições de campo na área agrícola de um produtor rural em Botucatu/SP. Os tratamentos utilizados foram: 1–Sem aplicação; 2–Água; 3–Preparado de Equisetum arvense; 4–Preparado de Equisetum hyemale; 5–Preparado de Equisetum giganteum; 6–Preparado Biodinâmico 501 (chifre-sílica). Observou-se maior eficiência do Preparado Biodinâmico 501 no controle da doença. O Preparado de Equisetum hyemale apresentou menor influência em relação aos tratamentos 3, 5 e 6. Portanto, o preparado biodinâmico 501 com alto conteúdo de sílica, teve maior efetividade no controle do carvão ou galha Tecaphora spilanthes e de Alternaria solani.
Alternative methods to control fungal diseases of jambu crop (Spilanthes oleracea L.) with Equisetum spp and biodynamic preparation 501
Keywords: Horsetail; Silicon; Jambu; Fungal illnesses; Biodynamic preparation 501; Cavalinha; Silício; Jambu; Doenças fúngicas; Preparado biodinâmico 501